2018
DOI: 10.1007/s13164-018-0404-5
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions About Colour Categories

Abstract: The origin of colour categories and their relationship to colour perception have been the prime example for testing the influence of language on perception and thought (Sapir-Whorf hypothesis) and more generally for investigating the biological, ecological and cultural determination of human cognition (nature-nurture debate). These themes are central to a broad range of disciplines, including vision research, neuroscience, cognitive psychology, developmental science, cultural anthropology, linguistics, compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 259 publications
(422 reference statements)
4
92
0
Order By: Relevance
“…Even within one culture, people vary in their choice of labels, when they describe colored items (e.g. Lindsey and Brown, 2014;Brown, Isse and Lindsey, 2016;Kuriki et al, 2017), or when they sort colors into categories (reviewed in: Witzel, 2018). Response times in categorization tasks are modulated by categorical membership of colors: people are faster in categorizing and naming colors with clear category membership than colors that are more ambiguous (Bornstein and Monroe, 1980;Zimmer, 1982).…”
Section: Using Response Times As a Measure Of Individual Variability mentioning
confidence: 99%
“…Even within one culture, people vary in their choice of labels, when they describe colored items (e.g. Lindsey and Brown, 2014;Brown, Isse and Lindsey, 2016;Kuriki et al, 2017), or when they sort colors into categories (reviewed in: Witzel, 2018). Response times in categorization tasks are modulated by categorical membership of colors: people are faster in categorizing and naming colors with clear category membership than colors that are more ambiguous (Bornstein and Monroe, 1980;Zimmer, 1982).…”
Section: Using Response Times As a Measure Of Individual Variability mentioning
confidence: 99%
“…Colorfulness might provide the missing link between color perception, color appearance, and color naming, a central topic in color science and in research on the relationship between perception and language (for review, see Siuda-Krzywicka, Boros, Bartolomeo, & Witzel, 2019;Witzel, 2018a;Witzel & Gegenfurtner, 2018b). Colorfulness is the attribute of a perceived color according to which the color appears to be more or less chromatic.…”
Section: Introductionmentioning
confidence: 99%
“…To explain the particular role of English prototypes it has been suggested that the prototypes of the English color categories are particularly ''salient'' and ''linguistically codable'' (Bolton, 1978;Boynton & Olson, 1990;Brown & Lenneberg, 1954;Hays, Margolis, Naroll, & Perkins, 1972;Rosch Heider, 1972;Sturges & Whitfield, 1997;Witkowski & Brown, 1982). Under the assumption that English category prototypes have a particular property due to which they correspond to the ''focus'' of universal color categories independent of language they were termed focal colors (Berlin & Kay, 1969;Rosch Heider, 1972; for review, see Witzel, 2018aWitzel, , 2018b. Regier, Kay, and Khetarpal (2007) showed that the different categories of a wide range of languages were distributed so that the color chips within the respective categories tended to be more similar than those across categories.…”
Section: Introductionmentioning
confidence: 99%
“…One side argues that a perceptual phenomenon gives rise to the formation of consistent categories across languages; the other argues that prior knowledge of language biases individuals' perception. The literature has yet to reach a consensus regarding what drives categorical perception [RK09,Wit18].…”
Section: Categorical Perception Of Colormentioning
confidence: 99%